Performance of the Pediatric Index of Mortality 2 in a pediatric intensive care unit - Lima, Antônio (Associação de Medicina Intensiva Brasileira, 2014)
OBJECTIVE: To assess the discrimination and calibration of the Pediatric Index of Mortality 2 in patients admitted to a pediatric intensive care unit. METHODS: The study was conducted with a contemporary cohort from November 2005 to November 2006. Patients aged 29 days to 18 years were included in the study. Patients who died within 12 hours of admission and cases of readmission were excluded from the study. The performance of the Pediatric Index of Mortality 2 was assessed by means of the Hosmer-Lemeshow goodness-of-fit test, the standardized mortality ratio and the area under receiver operating characteristic (ROC) curve with 95% confidence interval. The significance level was established as 5%. RESULTS: A total of 276 admissions to the pediatric intensive care unit were included in the analysis. The mortality rate was 14.13%, and the efficiency of admission 0.88%. The median age of the sample was 42.22 months, and most participants were male (60.1%). Most admissions were referrals from the emergency department. The mean duration of stay in pediatric intensive care unit was 6.43±5.23 days. Approximately 72.46% of admissions were for clinical reasons and exhibited an association with the outcome death (odds ratio: 2.9; 95%CI: 1.09-7.74; p=0.017). Calibration of the Pediatric Index of Mortality 2 with the chi-square statistic was 12.2686 (p=0.1396) in the Hosmer-Lemeshow goodness-of-fit test, and the standardized mortality ratio was 1.0. The area under the ROC curve assessing model discrimination was 0.778. CONCLUSION: Pediatric Index of Mortality 2 exhibited satisfactory performance.